2021
DOI: 10.1111/bph.15469
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of endocannabinoid transport in the brain

Abstract: The endocannabinoids 2-arachidonoylglycerol (2-AG) and anandamide are among the best studied lipid messengers in the brain. By activating cannabinoid receptors in the CNS, endocannabinoids tune synaptic function, thereby influencing a variety of physiological and behavioural processes. Extensive research conducted over the last few decades has considerably enhanced our understanding of the molecular mechanisms and physiological functions of the endocannabinoid system. It is now well-established that endocannab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 147 publications
0
20
0
Order By: Relevance
“…Because many reviews already exist that describe endocannabinoid (eCB) signaling (Toczek and Malinowska, 2018;Zou and Kumar, 2018;Cristino et al, 2020;Kaczocha and Haj-Dahmane, 2021), the risks of cannabis abuse (Ferland and Hurd, 2020;Hindley et al, 2020), and the potential cannabinoids may offer in psychiatric medicine (Amar, 2006;Black et al, 2019;Navarrete et al, 2020), our goal in the present manuscript is to describe how exogenous cannabinoids and eCBs influence dopamine (DA) signaling and behavior. While we will emphasize our own observations, we will also consider how they fit into the context of the general literature on reinforcement, appetitive behavior, adjunctive behavior, habit formation, and attentional processes.…”
Section: Statement Of Purposementioning
confidence: 99%
“…Because many reviews already exist that describe endocannabinoid (eCB) signaling (Toczek and Malinowska, 2018;Zou and Kumar, 2018;Cristino et al, 2020;Kaczocha and Haj-Dahmane, 2021), the risks of cannabis abuse (Ferland and Hurd, 2020;Hindley et al, 2020), and the potential cannabinoids may offer in psychiatric medicine (Amar, 2006;Black et al, 2019;Navarrete et al, 2020), our goal in the present manuscript is to describe how exogenous cannabinoids and eCBs influence dopamine (DA) signaling and behavior. While we will emphasize our own observations, we will also consider how they fit into the context of the general literature on reinforcement, appetitive behavior, adjunctive behavior, habit formation, and attentional processes.…”
Section: Statement Of Purposementioning
confidence: 99%
“…The lipophilic nature of eCBs necessitates a mechanism(s) that enables their translocation across the synaptic cleft from their site of synthesis to CB1Rs. Several mechanisms have been proposed to account for synaptic eCB transport, including FABP5 and extracellular vesicles (Kaczocha and Haj-Dahmane, 2021 ). We have previously shown that FABP5 is necessary for retrograde 2-AG signaling at glutamate synapses of DRn neurons (Haj-Dahmane et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is strong indirect evidence for the existence of this transmembrane transport, the molecular identity of the protein(s) involved remains to be assessed. In this context, several lipid-carrier proteins, which assist the movement of eCBs within and outside cells, have been identified, confirming that, despite the current controversy, the eCBs transport system should be further characterized in the future [ 71 , 72 ].…”
Section: The Endocannabinoid Systemmentioning
confidence: 92%